2016
DOI: 10.1021/acs.jpcb.6b08381
|View full text |Cite
|
Sign up to set email alerts
|

Can the Transport Properties of Molten Salts and Ionic Liquids Be Used To Determine Ion Association?

Abstract: There have long been arguments supporting the concept of ion association in molten salts and ionic liquids, largely based on differences between the conductivity and that predicted from self-diffusion coefficients by the Nernst-Einstein equation for noninteracting ions. It is known from molecular dynamics simulations that even simple models based on charged hard spheres show such a difference due to the (anti)-correlation of ion motions. Formally this is expressed as a difference between the velocity cross-cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
94
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(110 citation statements)
references
References 130 publications
16
94
0
Order By: Relevance
“…25 and 26 suggested to interpret RTILs as dilute electrolytes [49,50], assuming that most of the ions are ion paired. Theoretical [51][52][53][54], computational [52,[55][56][57][58][59] and experimental [26,27,60] papers have found that the extent of ion pairing in RTILs is not to the extent that was suggested in Refs. 25 and 26 (a detailed review of this work can be found in Refs.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…25 and 26 suggested to interpret RTILs as dilute electrolytes [49,50], assuming that most of the ions are ion paired. Theoretical [51][52][53][54], computational [52,[55][56][57][58][59] and experimental [26,27,60] papers have found that the extent of ion pairing in RTILs is not to the extent that was suggested in Refs. 25 and 26 (a detailed review of this work can be found in Refs.…”
Section: Introductionmentioning
confidence: 91%
“…61 and 62). It is almost widely accepted now that the extent of ion pairing suggested in that highly intriguing work [25] cannot be literally taken for RTILs, owing to a number of other physical properties not agreeing with that conclusion [3,53,56,63]. In fact, as summarised in Ref.…”
Section: Introductionmentioning
confidence: 96%
“…In this context, it is worth mentioning that Harris and coworkers calculated correlations functions of the ion dynamics in ionic liquid and molten salts from experimental diffusion and conductivity data. The underlying equations were based on the assumption of strict ion momentum conservation …”
Section: Case Studies Relevant For Energy Storage Technologiesmentioning
confidence: 99%
“…The deviations from it lead to smaller conductivities attributed to correlations and ion pairing [50]. This interpretation has been debated, with some authors suggesting that the concept of ion pairing and clustering in RTILs is not required [51,52] but some supporting it [53]. There have been investigations into the properties of ion pairs in RTILs [54], but we are not aware of any reports estimating the fraction of ions in a state that contribute to conductivity.…”
Section: Nature Of Compacity and Overscreening Vs Underscreeningmentioning
confidence: 99%